Peningkatan Keterampilan Membaca Pemahaman Isi Cerita Anak Melalui Media Handout Buku Bacaan Siswa Kelas V UPT SPF SD Inpres Bontomanai Kota Makassar - Sakina Sakina; Abd. Rahman Rahim; Haslinda Haslinda (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The problem in this research is: How do reading comprehension skills improve in concluding the contents of children's stories through developing reading book handouts for class V UPT SPF SD Inpres Bontomanai Makassar City students? The objectives of this research are; to determine the increase in learning outcomes in reading comprehension skills in concluding the content of children's stories through the development of reading book handouts for class V UPT SPF SD Inpres Bontomanai Makassar City students. The type of research used in this research is Classroom Action Research which consists of two cycles where each cycle is carried out in two meetings. The research subjects were teachers and students of class V UPT SPF SD Inpres Bontomanai, Makassar City, totaling 32 students consisting of 17 male students and 15 female students. The use of handout media can improve reading skills and understanding of the contents of children's stories in reading books for class V UPT SPF SD Inpres Bontomanai Makassar City. This can be seen from the results of the analysis of teacher activity observations in cycle I, namely 79.16% and increased in cycle II to 95.83%. Student activity also increased from 78% in cycle I to 95% in cycle II. Meanwhile, the results of the mastery test results in student learning outcomes in reading comprehension skills in cycle I were 37.5%, increasing to 87.5% in cycle II. Thus, it can be concluded that the use of handout media can improve reading skills, understanding the contents of children's stories, reading books for class V UPT SPF SD Inpres Bontomanai, Makassar City.